Trop2: Jack of All Trades, Master of None - Lenárt, Sára; Lenárt, Peter; Šmarda, Jan; Remšík, Ján; Souček, Karel; Beneš, Petr (Cancers, 2020)
Trophoblast cell surface antigen 2 (Trop2) is a widely expressed glycoprotein and an epithelial cell adhesion molecule (EpCAM) family member. Although initially identified as a transmembrane protein, other subcellular localizations and processed forms were described. Its congenital mutations cause a gelatinous drop-like corneal dystrophy, a disease characterized by loss of barrier function in corneal epithelial cells. Trop2 is considered a stem cell marker and its expression associates with regenerative capacity in various tissues. Trop2 overexpression was described in tumors of different origins; however, functional studies revealed both oncogenic and tumor suppressor roles. Nevertheless, therapeutic potential of Trop2 was recognized and clinical studies with drug-antibody conjugates have been initiated in various cancer types. One of these agents, sacituzumab govitecan, has been recently granted an accelerated approval for therapy of metastatic triple-negative breast cancer. In this article, we review the current knowledge about the yet controversial function of Trop2 in homeostasis and pathology.